Drosophila CRISPR/Cas9 mutants as tools to analyse cardiac filamin function and pathogenicity of human FLNC variants. - Ader, F.; Russi, M.; Tixier-Cardoso, L.; Jullian, E.; Martin, E.; Richard, P.; Villard, E.; Monnier, V. (Biology open, 2022)
Filamins are large proteins with actin-binding properties. Mutations in FLNC, one of the three filamin genes in humans, have recently been implicated in dominant cardiomyopathies, but the underlying mechanisms are not well understood. Here, we aimed to use Drosophila melanogaster as a new in vivo model to study these diseases. First, we show that adult-specific cardiac RNAi-induced depletion of Drosophila Filamin (dFil) induced cardiac dilatation, impaired systolic function and sarcomeric alterations, highlighting its requirement for cardiac function and maintenance of sarcomere integrity in the adult stage. Next, we introduced in the cheerio gene, using CRISPR/Cas9 gene editing, three missense variants, previously identified in patients with hypertrophic cardiomyopathy. Flies carrying these variants did not exhibit cardiac defects or increased propensity to form filamin aggregates, arguing against their pathogenicity. Finally, we show that deletions of the C-term part of dFil carrying the last four Ig-like domains are dispensable for cardiac function. Collectively, these results highlight the relevance of this model to explore the cardiac function of filamins and increase our understanding of physio-pathological mechanisms involved in FLNC-related cardiomyopathies. This article has an associated First Person interview with the first author of the paper.